Does Services Liberalization Benefit Manufacturing Firms? Evidence from the Czech Republic - Arnold, Jens; Javorcik, Beata S.; Mattoo, Aaditya (World Bank, Washington, DC, 2012)
While there is considerable empirical evidence on the impact of liberalizing trade in goods, the effects of services liberalization have not been empirically established. Using firm-level data from the Czech Republic for the period 1998-2003, this study examines the link between services sector reforms and the productivity of domestic firms in downstream manufacturing. Several aspects of services reform are considered and measured, namely, the increased presence of foreign providers, privatization, and enhanced competition. The manufacturing-services linkage is measured using information on the degree to which manufacturing firms in a particular industry rely on intermediate inputs from specific services sectors. The econometric results lead to two conclusions. First, the study finds that services policy matters for the productivity of manufacturing firms relying on services inputs. This finding is robust to several econometric specifications, including controlling for unobservable firm heterogeneity and for other aspects of openness. Second, it finds evidence that opening services sectors to foreign providers is a key channel through which services liberalization contributes to improved performance of downstream manufacturing sectors. This finding is robust to instrumenting for the extent of foreign presence in services industries. As most barriers to foreign investment today are not in goods but in services sectors, the findings may strengthen the argument for reform in this area.